Protovarys in theory, tetraphonos in practice?: preliminary observations on an archaeology of the Varys’ intervallics - Savvas, Georgios (Epistēmēs Metron Logos, 2021)
This paper opens with a caveat: as denoted in the title, its intention is not to be exhaustive on its subject, as of yet (future publication soon to follow). Attempted will be the exposition and commentation upon a series of indications regarding the intervallics of the plagal third mode, commonly referred to in the sources as Varys (low; due to being the mode with the lowest basis/ison in the ecclesiastical eight-mode system, Octoechos). If these result to a reacquaintance with the mode and a reconsideration of some of its intervallic possibilities, then the paper will have been successful in its intentions.